If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 7 = 20x + -7 Reorder the terms: 7 + 9x = 20x + -7 Reorder the terms: 7 + 9x = -7 + 20x Solving 7 + 9x = -7 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 7 + 9x + -20x = -7 + 20x + -20x Combine like terms: 9x + -20x = -11x 7 + -11x = -7 + 20x + -20x Combine like terms: 20x + -20x = 0 7 + -11x = -7 + 0 7 + -11x = -7 Add '-7' to each side of the equation. 7 + -7 + -11x = -7 + -7 Combine like terms: 7 + -7 = 0 0 + -11x = -7 + -7 -11x = -7 + -7 Combine like terms: -7 + -7 = -14 -11x = -14 Divide each side by '-11'. x = 1.272727273 Simplifying x = 1.272727273
| 12.50+40= | | -2+v=4 | | 1.98=(8.99*10^9)*(11.7*10^-6)*(29.9*10^-6)/r^2 | | -2z-7y=7+7 | | 4x-12x+3=5 | | x-2(-2x+5)=2 | | 12x+22=-9x-41 | | -144=-8x | | 3n-8=32n | | x=ky+f | | 6x-99=-5x | | 4(x-1)+3(x+1)= | | 217.25=3 | | 4x-(2x+5)=3x-10 | | 6m-6=6m+18 | | 2x+3x+3=-12 | | 21p-62=38+p | | 8x+12-2x-5=3 | | y=kx+f | | 2(2+5x)=9(x-1) | | 81c^2+18c+1= | | 9[5-7(x-1)]+6[(5x+7)-8]=11x-336 | | (1-5j)+(-2-6j)=-1-11j | | 6x+x^2=84 | | 9c^2-8c-1= | | 4-x=4x+19 | | -3(x+3)=5x | | 0.004(2-k)+0.09(k-7)=1 | | 1x+4x=43 | | 13-4x+12=13 | | 4t-3=37-t | | 5b-7=-13 |